The four Problems of Economic Institutions and the Socialist of Economic Calculation Debate - Batista, José Hamilton dos Santos (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2019)
The present work has as its objective the elaboration of an analytical framework to organize the relations of economic institutions issues, as well as their application to the issue of the socialist economic calculation, proposing a reading on the discussion. Little was analyzed about the relationship of the issues, which led to a language barrier hindering the understanding of Mises and Hayek’s proposals. The investigation of such issues will be guided by Bartley-Popper’s principles of Pancritical Rationalism, where the institutions’ analysis as rules allowing greater or lesser learning capacity of a system, is transferred to the economic issues and allows to clarify the two most controversial issues of the discussion: knowledge and its use. If the article succeeds in clarifying such issues, a framework emerges naturally as to how issues fit together and where different proposals for socialism fail.